The Impact of Using Drama in Teaching Arabic Syntax on the Achievement Among Tenth Grade Female Students - Al-kukhun, Amin; Hania, Lina (Jordan Journal of Educational Sciences, 2009)
This study aimed at measuring the effect of using drama in teaching Arabic syntax on the achievement among tenth grade female students compared with teaching them by the traditional class method. The study used selective sampling. The sample consisted of (120) female tenth grade students from two schools. The sample was chosen from four sections. The students divided equally into an experimental group (60 female students), and control group (60 female students). The experimental group was taught the Syntax by using drama whereas the control group was taught by the traditional method. The text-based instructional material for the experimental group was prepared by the researchers from a unit in the Arabic syntax textbook for the tenth grade. To answer the study question, the researchers prepared an achievement test which was administrated for both the experimental and the control groups. For data analysis, the researchers used ANCOVA to compare the post-test score means of the experimental and the control groups after removing the impact of the pre-test scores. The study found that there were statistically significant differences between the achievements of the two groups at (α=0.05) in a favor of the experimental group, which had been instructed through the drama method..(